2020
DOI: 10.1027/1015-5759/a000531
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Other-Directed, Lighthearted, Intellectual, and Whimsical Playfulness in Adults

Abstract: Abstract. Adult playfulness is an individual differences variable that allows people to (re-)frame everyday situations in a way to make them entertaining, stimulating, and/or interesting. Recently, a structural model with four facets (i.e., Other-directed, Lighthearted, Intellectual, and Whimsical; OLIW) and a subjective measure with 28 items have been developed. The main aim of this study is to test a 12-item short form (OLIW-S). In Study 1, we retrieved the 4-factorial OLIW structure in three independently c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 36 publications
10
21
0
Order By: Relevance
“…First, this is in stark contrast to Zuckerman (1994), who found strong correlations between the hedonic-oriented Need for Play scale (Jackson, 1974) and the SSS facet Disinhibition. However, this is in line with prior findings about the independence (Otherdirected and Intellectual playfulness) or negligible overlap with the Disinhibition domain of Krueger et al's (2012) personality inventory of maladaptive personality traits (Proyer et al, 2020). Second, this pattern fits well into laypeople's notions of playfulness, i.e., providing a means to explore new situations and preventing routine (e.g., Barnett, 2007;Proyer, 2014), and lends evidence to the notion of playfulness and SS sharing inclinations to exploration.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…First, this is in stark contrast to Zuckerman (1994), who found strong correlations between the hedonic-oriented Need for Play scale (Jackson, 1974) and the SSS facet Disinhibition. However, this is in line with prior findings about the independence (Otherdirected and Intellectual playfulness) or negligible overlap with the Disinhibition domain of Krueger et al's (2012) personality inventory of maladaptive personality traits (Proyer et al, 2020). Second, this pattern fits well into laypeople's notions of playfulness, i.e., providing a means to explore new situations and preventing routine (e.g., Barnett, 2007;Proyer, 2014), and lends evidence to the notion of playfulness and SS sharing inclinations to exploration.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, there is evidence that playfulness goes along with cognitive, social, and behavioral spontaneity, inclinations to impulsivity, and thinking styles that are denoted by novelty and low planning (e.g., Lieberman, 1977;Proyer, 2017;Proyer et al, 2019b). In line with such findings, the localization of the OLIW facets in a classification system of maladaptive personality traits (PID-5; Krueger et al, 2012) showed that Whimsical playfulness is related robustly to the Disinhibition domain, which is, among others, characterized by risk-taking (Proyer et al, 2020). Playfulness relates to exploration behaviors among humans and animals (e.g., Weisler and McCall, 1976;Lieberman, 1977;Panksepp, 1998;Shen, 2020), and Singer and Rummo (1973) found that children's playfulness is positively related to behaviors coded as novelty seeking/curiosity.…”
Section: The Present Studymentioning
confidence: 73%
See 2 more Smart Citations
“…When testing their overlap with broad personality traits such as the Big Five, there is the expected overlap but no redundancy (e.g., Proyer, 2012Proyer, , 2017. Studies using the OLIW model have shown the differential associations between the four facets with numerous outcomes such as subjective well-being, mental and physical health (e.g., Farley et al, 2021;Proyer, 2014b;Proyer et al, 2018bProyer et al, , 2020, sensation seeking (Brauer et al, 2021b), and creative thinking styles (e.g., Proyer et al, 2019b) to name but a few.…”
Section: Adult Playfulnessmentioning
confidence: 99%